Analisis Kelayakan Usahatani Cabai Rawit Di Kabupaten Lampung Selatan - Aryan Ari Sepri YH (AGRISUSTAIN : Journal of Agribusiness and Sustainable Agriculture, 2025)
Cayenne pepper are one of the most widely consumed horticultural commodities by the public and are economically very important. The main issue faced by farmers is the presence of pests and diseases that often attack and disrupt the growth of cayenne pepper plants, leading to a decline in quality and productivity, which in turn causes losses for farmers. The aims of this study is to determine the costs, revenues, incomes, profit, and feasibility of cayenne pepper farming in South Lampung Regency. The research was conducted in Tajimalela Village, Kalianda District, South Lampung Regency, with a sample size of 25 farmers. The method used is quantitative analysis. The results of this study show that the total cost incurred by farmers was IDR 15,444,415. The revenue obtained was IDR 30,464,329, while the income amounted to IDR 18,250,433, and the profit was IDR 15,019,914. The R/C Ratio value was 1.97, indicating that cayenne pepper farming in South Lampung Regency is feasible and profitable.